Method for preparing anisotropic composite material through hot pressing
Through powder metallurgy technology, La-Fe-Si alloy is mixed with high entropy alloy CrMnFeCoNi and prepared into an anisotropic composite material by hot pressing, which solves the thermal conductivity and mechanical properties of La-Fe-Si alloy in the application of refrigeration technology. The problem is that efficient heat exchange and excellent mechanical properties are achieved.
Patent Information
- Application Number
- CN202311045144.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-18
- Publication Date
- 2025-02-21
AI Technical Summary
La-Fe-Si alloys have problems with thermal conductivity and mechanical properties in the application of refrigeration technology. The thermal conductivity of single-phase alloys is insufficient and the volume sudden change in the first-order phase transition is likely to cause cracks, affecting heat transfer and working efficiency.
Through powder metallurgy technology, La-Fe-Si-based alloy and high-entropy alloy CrMnFeCoNi are mixed in a certain proportion, and prepared into anisotropic composite material by hot pressing, optimizing the shape and distribution of the second phase to improve the thermal conductivity of the material and mechanical properties.
The high thermal conductivity and excellent mechanical properties of composite materials are achieved, which reduces the risk of cracks, improves the heat exchange efficiency and the application value of the material.
Smart Images

Figure CN119489192A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of magnetic refrigeration materials, and in particular to a method for preparing a composite material by powder metallurgy. Background Art
[0002] La-Fe-Si alloy has the advantages of large magnetocaloric effect, non-toxicity and low raw material cost, and is expected to be put into practical application as a new type of refrigeration material. At present, there are two main limitations on the practical application of La-Fe-Si alloy in refrigeration technology:
[0003] (1) Thermal conductivity. The maximum thermal conductivity of a single-phase La-Fe-Si alloy is about 6 W / m K, which is much lower than the 50 W / m K required for a refrigerator to achieve maximum cooling power at a 2 Hz operating frequency. Therefore, La-Fe-Si alloys need to be designed into complex geometric shapes with high specific surface areas in applications to achieve more efficient heat exchange.
[0004] (2) Mechanical properties. The large volume mutation during the primary phase transformation of La-Fe-Si alloy is easy to introduce cracks. As the number of cycles increases, the cracks tend to increase and expand, destroying the mechanical integrity, affecting heat transfer, and reducing work efficiency. La-Fe-Si alloy is usually compounded with other materials (such as metals, polymers, etc.) to solve these problems.
[0005] In composite materials, the anisotropy of some properties can be achieved by optimizing the shape and distribution of the second phase. In the study of La-Fe-Si composite materials, there are few studies on the influence of the shape and distribution of the second phase on the performance of the composite materials. If we can take advantage of the good performance of La-Fe-Si alloys and second-phase alloys themselves, while regulating some properties, La-Fe-Si composite materials can be better put into practical applications, which has important research significance. If the second-phase alloy has good rheological properties, by regulating the pressure and temperature during the powder metallurgy process, it can form a certain shape in the composite material and arrange it along certain directions, anisotropic composite materials can be obtained, in which special orientation may optimize the performance of the material and enhance the application value of the material.
[0006] High entropy alloys have high strength and hardness, good thermal stability and corrosion resistance, good fatigue strength and fracture strength, and good rheological properties at high temperatures. Taking advantage of this, we prepared La-Fe-Si alloy and high entropy alloy composites through powder metallurgy, and studied their magnetic properties and mechanical properties through relevant tests. From the aspects of element distribution, second phase shape, mechanical properties, etc., combined with factors such as second phase properties and preparation conditions, the source of its performance changes was explained. How to select appropriate process parameters to prepare composite alloys with different element distributions according to the special needs of composite alloys has become one of the difficulties that must be overcome for large-scale application of this alloy.
[0007] The problem with the closest existing technology is that it mainly seeks metals with lower melting points, excellent mechanical properties and high thermal conductivity through hot pressing, while improving their mechanical properties and thermal conductivity to a certain extent while maintaining their good magnetocaloric properties as much as possible. Summary of the invention
[0008] In order to improve the mechanical properties and thermal conductivity, the present invention aims to provide a method for preparing anisotropic composite materials by hot pressing.
[0009] The technical solution to achieve the purpose of the present invention is:
[0010] A method for preparing anisotropic composite materials by hot pressing comprises the following steps: La-Fe-Si based alloy powder with a certain particle size and CrMnFeCoNi alloy powder with a certain particle size are mixed in proportion, and then hot pressed to form a cylindrical composite material.
[0011] Preferably, the La-Fe-Si based alloy powder is La 0.7 Ce 0.3 Fe 11.45 Mn 0.15 Si 1.4 .
[0012] Preferably, the particle size of the La-Fe-Si based alloy powder is 54-75 μm.
[0013] Preferably, the particle size of the CrMnFeCoNi alloy powder is 54-100 μm.
[0014] Preferably, La-Fe-Si based alloy powder with a certain particle size and CrMnFeCoNi alloy powder with a certain particle size are mixed in a mass ratio of 3:1 and then hot-pressed to form a cylindrical composite material.
[0015] Preferably, the hot pressing pressure is 3-6 Gpa, the hot pressing temperature is 700-1200° C., and the hot pressing time is 8-18 min.
[0016] Preferably, the La-Fe-Si based alloy powder and the CrMnFeCoNi alloy powder are prepared by arc melting, spray casting, belt spinning and grinding into powder in sequence.
[0017] Preferably, the main phase of the anisotropic composite material is a 1:13 pure phase of La-Fe-Si alloy, and the second phase is a fcc pure phase.
[0018] Compared with the prior art, the present invention has the following advantages:
[0019] (1) Powder metallurgy: Two alloy powders of a certain size are evenly mixed in a certain proportion to form a composite material through powder metallurgy. La-Fe-Si is composited with CrMnFeCoNi, and more Co elements diffuse into the 1:13 phase of the La-Fe-Si alloy, which reduces the magnetic properties of the alloy.
[0020] (2) La-Fe-Si alloy blocks were prepared by arc melting and crushed into powders, which were then mixed with polymers in a ratio of 1:1 and naturally solidified under different magnetic fields to form composite materials. Under a rotating magnetic field with a speed of 60 r / min, 50 wt.% La-Fe-Si and 50 wt.% (epoxy resin + graphene) polymer were mixed. Under the combined influence of magnetic force, polymer viscosity resistance and particle interaction force, the La-Fe-Si powder and polymer in the composite material were rearranged. A relatively obvious layered distribution consistent with the theoretical model was observed in the prepared composite material, and its thermal diffusivity was anisotropic. The addition of graphene improved the thermal diffusivity to a certain extent. The change in the magnetic properties of the composite material is mainly caused by the removal of part of the internal strain and grain boundaries when the particle size of the La-Fe-Si alloy is reduced, the weakening of the first-order phase transformation, and the increase in the specific surface area of the sample. Different phase distributions have little effect on the magnetic properties of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is a schematic diagram of the principle of the six-sided hot press mold involved in the present invention.
[0022] Figure 2 It is an X-ray schematic diagram of the sample contact roll surface and back roll surface of Example 1 (Sample 1) and Example 2 (Sample 2) of the present invention.
[0023] Figure 3 Schematic diagram of the cross section and longitudinal section of the sample of Example 1 of the present invention under scanning electron microscope.
[0024] Figure 4 This is a schematic diagram of the cross-section and longitudinal section of the sample of Example 2 involved in the present invention under a scanning electron microscope.
[0025] Figure 5 This is the sample element distribution diagram of Example 1 involved in the present invention.
[0026] Figure 6 This is the sample element distribution diagram of Example 2 involved in the present invention.
[0027] Figure 7 This is the simulated strain distribution cloud diagram of pyrophyllite assembly block. DETAILED DESCRIPTION
[0028] The present invention will be further described in detail below in conjunction with the embodiments of the accompanying drawings. It should be pointed out that the embodiments described below are intended to facilitate the understanding of the present invention and do not have any limiting effect on the present invention.
[0029] The concept of the present invention is:
[0030] The present invention studies the reasons for the changes in the Curie temperature and magnetocaloric properties of the composite material by analyzing the preparation conditions, X-ray diffraction patterns, and element distribution. For La-Fe-Si and CrMnFeCoNi composite materials, since the Co element diffuses more during the powder metallurgy process, the Co element enters the 1:13 phase of the La-Fe-Si alloy, which reduces the Curie temperature of the alloy, slows down the phase change process, and expands the phase change temperature zone. For La-Fe-Si and CrMnFeNi composite materials, since they do not contain the Co element, although other elements also diffuse to a certain extent during the powder metallurgy process, the influence on their Curie temperature, phase change, etc. is small. At the same time, it is found that the size of the La-Fe-Si alloy powder in the raw material has a greater influence on the Curie temperature and magnetocaloric properties of the composite material. When the size of the La-Fe-Si alloy powder is small, the 1:13 phase in the La-Fe-Si alloy is destroyed during the powder metallurgy process, and the element diffuses more, thereby destroying the magnetocaloric properties of the alloy.
[0031] By analyzing the shape and distribution of the second phase in different cross-sectional scans, as well as the stress-strain curves of the composite materials in different directions, combined with the distribution cloud of pyrophyllite in the six-sided hot press chamber and the physical properties of the La-Fe-Si matrix and the second phase, the reasons for the differences in mechanical properties of the composite materials in different directions were studied. During the pressurization process of powder metallurgy, due to the different pressure transmission efficiencies in the vertical and horizontal directions, the second phase produces different degrees of plastic deformation in different directions. The lamellar distribution of the second phase in the prepared composite material has a certain directionality, so there is a large difference in the mechanical properties in the horizontal and vertical directions. The maximum compressive strength in the vertical direction is 391.91MPa, which is 2.41 times that in the horizontal direction, and the maximum compressive strain in the vertical direction is 3.88%, which is 1.61 times that in the horizontal direction.
[0032] The anisotropic composite material prepared by hot pressing according to the present invention comprises the following steps:
[0033] Step 1: According to La 0.7 Ce0.3 Fe 11.45 Mn 0.15 Si 1.4 Weigh the corresponding raw material according to the chemical formula of CrMnFeCoNi and name it as raw material 1; weigh the corresponding raw material according to the chemical formula of CrMnFeCoNi and name it as raw material 2;
[0034] Step 2, arc melting the raw material 1 and the raw material 2 respectively to prepare La-Fe-Si based alloy ingot and CrMnFeCoNi alloy ingot with uniform composition;
[0035] Step 3, respectively using spray casting to make two alloy bars from the two alloy ingots obtained in step 2;
[0036] Step 4, sealing the alloy bars, performing heat treatment, and then water quenching;
[0037] Step 5, respectively preparing alloy strips by using the strip-spinning method with the materials obtained in step 4;
[0038] Step 6, grinding off the surface oxide layer of the alloy strips, grinding into La-Fe-Si based alloy powder and CrMnFeCoNi alloy powder, and sieving them respectively;
[0039] Step 7: Mix the sieved alloy powders and hot-press them to form a cylindrical composite material.
[0040] Embodiment 1:
[0041] Step 1: According to La 0.7 Ce 0.3 Fe 11.45 Mn 0.15 Si 1.4 Weigh the corresponding raw materials according to the chemical formula of CrMnFeCoNi in the ratio of 3:1;
[0042] Step 2: Place the above raw materials in an arc melting furnace, reduce the vacuum to below 5 Pa, fill with Ar gas until the pressure in the chamber is 0.05 Pa, and then reduce the vacuum to below 5 Pa. Repeat the above gas washing steps twice and reduce the vacuum to 1×10 - 3 Pa, introduce Ar gas until the pressure in the chamber is 0.05 Pa. Slowly add current until the sample is completely melted and continue melting for about 1 minute. After the sample cools down, turn the sample over and repeat the melting 4 times.
[0043] Step 3: Use a grinder to grind off the surface oxide scale of the alloy ingots obtained in step 2. Place the alloy ingot in a quartz tube with an opening at the lower end, wash and evacuate, introduce Ar gas until the pressure in the chamber is 0.05 Pa, quickly increase the current to 10-15A and maintain for about 30 seconds. When the sample is in a molten state and is about to flow out of the quartz tube, use the pressure difference between the atmospheric pressure in the quartz tube and the 0.05Pa in the vacuum belt furnace chamber to spray the sample into the mold, and obtain La 2+ with a diameter of 4 mm. 0.7 Ce 0.3 Fe 11.45 Mn 0.15 Si 1.4 Alloy rods and CrMnFeCoNi alloy rods.
[0044] Step 4: The alloy bars obtained in step 3 are sealed and heat treated respectively, with an annealing temperature of 1353 K, an annealing time of 7 days, and quenching in ice water.
[0045] Step 5: Polish the surface of the alloy rod obtained in step 4, cut the alloy rod into small pieces with a mass of about 5 g using a wire cutting machine, and then melt the block sample in a vacuum belt spinning machine at a linear speed of 25 m / s and spin it to prepare La 0.7 Ce 0.3 Fe 11.45 Mn 0.15 Si 1.4 alloy strip and CrMnFeCoNi alloy strip.
[0046] Step 6: Use sandpaper to remove the surface oxide layer of the alloy strip, and then grind it into La 0.7 Ce 0.3 Fe 11.45 Mn 0.15 Si 1.4 alloy powder and CrMnFeCoNi alloy powder.
[0047] Step 7: Use a sieve to filter out 54-75μm La 0.7 Ce 0.3 Fe 11.45 Mn 0.15 Si 1.4 Alloy powder (La-Fe-Si) is used as the main phase, and CrMnFeCoNi alloy powder of 54-100 μm is selected as the second phase. The selected La-Fe-Si powder is evenly mixed with CrMnFeCoNi powder, and an anisotropic composite material is prepared by hot pressing. Figure 1 This is the schematic diagram of the six-sided hot press used for powder metallurgy. The hot pressing pressure is 3Gpa, the hot pressing temperature is 800℃, and the hot pressing time is 10min.
[0048] The following tests are performed on anisotropic composite materials:
[0049] Using X-ray diffraction patterns, Figure 2 It can be seen that the main phase of the composite material is a 1:13 pure phase of La-Fe-Si alloy, containing very little α-Fe impurity phase, and the second phase is a fcc pure phase. The diffraction peak of the prepared composite material phase is offset compared to the diffraction peak of the raw material phase, indicating that the phases of the two raw materials have been affected to a certain extent during the metallurgical process.
[0050] Embodiment 2:
[0051] The hot pressing temperature in step 7 of Example 1 was changed from 800°C to 1050°C, and the other steps were the same as in Example 1.
[0052] The following tests are performed on anisotropic composite materials:
[0053] The prepared composite material was tested using an X-ray diffractometer, and the results were consistent with the conclusions obtained in Example 1. The diffraction peaks were offset compared to the diffraction peaks of the raw material phases. During the powder metallurgy process, the phases of the two raw materials were affected to a certain extent.
[0054] The microscopic morphology of the samples of Example 1 and Example 2 was observed using a scanning electron microscope. The cross-sectional and longitudinal sectional morphologies of Example 1 and Example 2 were as follows: Figure 3 and Figure 4 As shown, the element content was then analyzed using the point scanning mode of the energy spectrometer in the scanning electron microscope. The results are shown in Figure 5 and Figure 6 As shown in the figure, it can be concluded that during the powder metallurgy process, the elements in the second phase diffused into the main phase, among which Cr, Mn, Fe, Ni and other elements diffused relatively less, while Co diffused more; La, Ce, Fe, Mn, Si elements in the main phase also diffused a small amount into the second phase. Therefore, during the powder metallurgy process, mutual diffusion of elements occurred between the main phase and the second phase, which is the main reason for a certain shift in the diffraction peak of the La-Fe-Si composite material sample phase.
[0055] The compositions and hot pressing parameters of the anisotropic composite materials prepared in Example 1 and Example 2 are shown in Table 1.
[0056] Table 1
[0057]
[0058] From the above experiments we can know:
[0059] The difference in the shape of the second phase in the cross-sectional and longitudinal morphologies of the composite material is mainly caused by the properties of the two phases and the pressure and temperature in the powder metallurgy process. For the six-sided hot press used in powder metallurgy, the finite element simulation analysis shows that the distribution of the pressure field inside the cavity is uneven during the powder metallurgy synthesis process. The simulation results are as follows: Figure 7 As shown in the figure, although the six directions of the six-sided hot press are simultaneously pressurized during the powder metallurgy process, the materials of the pyrophyllite mold at different positions where the powder sample is placed are different, resulting in different pressure transmission efficiencies. As can be seen from the figure above, the outside of the horizontal direction is completely wrapped by pyrophyllite, and the inside is in contact with the graphite furnace, while the vertical direction is only partially wrapped by pyrophyllite. The central area of the upper and lower surfaces is wrapped by a conductive steel ring. Due to the high pressure transmission efficiency of the conductive steel ring material, the pressure transmission in the vertical direction during the powder metallurgy process is greater than that in the horizontal direction. Therefore, the large difference in the shape of the CrMnFeNi phase in the cross section and the longitudinal section is mainly caused by the different forces in different directions during the powder metallurgy process. For the six-sided hot press, pressure is applied first and then the temperature is increased. Previous studies have found that at a certain strain rate, the flow stress and strain hardening of high entropy alloys decrease as the deformation temperature increases. In the process of increasing pressure, the pressure transmission efficiency in the horizontal and vertical directions is different, and the second phase undergoes different degrees of plastic deformation in different directions. Then the temperature is raised and kept at 1050℃, La-Fe-Si softens and forms phases at 1050℃, and the main phase and the second phase are bonded together during the continuous heat preservation and pressure holding process. The second phase distribution in the cross section of the composite material finally prepared is a sheet with a large area and uniform length and width, and the second phase distribution in the longitudinal section is a small and elongated strip.
[0060] In summary, the large difference in the shape of the second phase in the cross-sectional and longitudinal cross-sectional morphology of the composite materials corresponding to Sample 1 and Sample 2 in the present invention is mainly caused by the different forces in different directions during the powder metallurgy process. In addition, the second phase in the longitudinal cross-sectional morphology of Sample 2 is more elongated and has a more obvious directionality than the second phase in the longitudinal cross-sectional morphology of Sample 1, mainly because the temperature and pressure of Sample 2 during the powder metallurgy process are higher than those of Sample 1, so the degree of plastic deformation of the second phase is greater.
Claims
1. A method for preparing an anisotropic composite material by hot pressing, characterized in that: The method comprises the following steps: mixing La-Fe-Si based alloy powder with a certain particle size and CrMnFeCoNi alloy powder with a certain particle size in proportion, and then hot pressing the mixture to form a cylindrical composite material.
2. The method according to claim 1, characterized in that La-Fe-Si based alloy powder is La 0.7 Ce 0.3 Fe 11.45 Mn 0.15 Si 1.4 .
3. The method according to claim 1, characterized in that The particle size of La-Fe-Si based alloy powder is 54~75μm.
4. The method according to claim 1, characterized in that The particle size of CrMnFeCoNi alloy powder is 54~100μm.
5. The method according to claim 1, characterized in that La-Fe-Si based alloy powder with a certain particle size and CrMnFeCoNi alloy powder with a certain particle size are mixed in a mass ratio of 3:1 and then hot pressed to form a cylindrical composite material.
6. The method according to claim 1, characterized in that The hot pressing pressure is 3-6Gpa, the hot pressing temperature is 700-1200°C, and the hot pressing time is 8-18min.
7. The method according to claim 1, characterized in that The La-Fe-Si based alloy powder and the CrMnFeCoNi alloy powder are prepared by arc melting, spray casting, strip spinning and grinding into powder in sequence.
8. An anisotropic composite material prepared by the method according to any one of claims 1 to 7.
9. The anisotropic composite material according to claim 8, characterized in that: The main phase of the anisotropic composite material is a 1:13 pure phase of La-Fe-Si alloy, and the second phase is a fcc pure phase.